Role of DFNB1 mutations in hereditary hearing loss among assortative mating hearing impaired families from South India - Pavithra Amritkumar; Justin Margret Jeffrey; Jayasankaran Chandru; Paridhy Vanniya S; M. Kalaimathi; Rajagopalan Ramakrishnan; N. P. Karthikeyen; C. R. Srikumari Srisailapathy (BMC, 2018)
Abstract Background DFNB1, the first locus to have been associated with deafness, has two major genes GJB2 & GJB6, whose mutations have played vital role in hearing impairment across many ethnicities in the world. In our present study we have focused on the role of these mutations in assortative mating hearing impaired families from south India. Methods One hundred and six assortatively mating hearing impaired (HI) families of south Indian origin comprising of two subsets: 60 deaf marrying deaf (DXD) families and 46 deaf marrying normal hearing (DXN) families were recruited for this study. In the 60 DXD families, 335 members comprising of 118 HI mates, 63 other HI members and 154 normal hearing members and in the 46 DXN families, 281 members comprising of 46 HI and their 43 normal hearing partners, 50 other HI members and 142 normal hearing family members, participated in the molecular study. One hundred and sixty five (165) healthy normal hearing volunteers were recruited as controls for this study. All the participating members were screened for variants in GJB2 and GJB6 genes and the outcome of gene mutations were compared in the subsequent generation in begetting deaf offspring. Results The DFNB1 allele frequencies for DXD mates and their offspring were 36.98 and 38.67%, respectively and for the DXN mates and their offspring were 22.84 and 24.38%, respectively. There was a 4.6% increase in the subsequent generation in the DXD families, while a 6.75% increase in the DXN families, which demonstrates the role of assortative mating along with consanguinity in the increase of DFNB1 mutations in consecutive generations. Four novel variants, p.E42D (in GJB2 gene), p.Q57R, p.E101Q, p.R104H (in GJB6 gene) were also identified in this study. Conclusion This is the first study from an Indian subcontinent reporting novel variants in the coding region of GJB6 gene. This is perhaps the first study in the world to test real-time, the hypothesis proposed by Nance et al. in 2000 (intense phenotypic assortative mating mechanism can double the frequency of the commonest forms of recessive deafness [DFNB1]) in assortative mating HI parental generation and their offspring.